History of Various Classifications of Gastritis - Sung Kyun Yim; Seung Young Seo (Yong Chan Lee, 2023)
Gastritis is common worldwide. The combination of Helicobacter pylori (H. pylori) infection with background gastritis, including atrophic gastritis or intestinal metaplasia is implicated as an important etiopathogenetic contributor to gastric cancer. Since the gastritis classification proposed by Schindler, research has focused on classification of gastritis for accurate diagnosis and prediction of prognosis. Advances in endoscopic technology have enabled more accurate visualization of the gastric mucosa and 'targeted' biopsies with the emergence of newer classifications based on visual findings (Kimura-Takemoto classification) and more specific histopathological findings using targeted biopsies (Whitehead classification). Following the discovery of H. pylori, it is mandatory to consider its role as an important contributor to gastritis. Therefore, it was necessary to redefine the classification of gastritis and arrive at a consensus, which led to the establishment of an international consensus classification, referred to as the Sydney system. However, the Sydney system alone cannot predict the gastric cancer risk, and scoring systems such as the Operative Link for Gastritis Assessment and the Operative Link on Gastritis Assessment based on Intestinal Metaplasia were proposed. These systems are based on histopathological findings observed in endoscopic biopsy specimens. However, availability of high-definition images following technological advances has facilitated the emergence of a visual classification, the Kyoto classification. In contrast to the Sydney system, the Kyoto classification is based exclusively on interpretation of visual findings and focuses on detection of H. pylori infection and gastric cancer prediction. In this review, we summarize the history and background of the various classifications of gastritis.